Familial congenital lower urinary tract obstruction (LUTO) suggested by screening for lower urinary tract dysfunction in parents of patients: A descriptive study - Ebach, Fabian; Wagner, Pauline; Stein, Raimund; Dolscheid-Pommerich, Ramona; Reutter, Heiko Martin; Hilger, Alina Christine (Health Science Reports, 2024)
Background: Congenital lower urinary tract obstruction (LUTO) describes a heterogeneous group of congenital malformations. Posterior urethral valves (PUV) represent the most common entity. Familial occurrence has been described, suggestive of underlying genetic factors. LUTO can occur in various degrees of severity. In severe forms, oligohydramnios, pulmonary hypoplasia, and renal damage can occur resulting in high pre- and postnatal mortality. On the contrary, mild forms may become apparent through recurrent urinary tract infections. Such high phenotypic variability has been described even within the same family. Here, we systematically screened parents of affected children for symptoms of LUTO. Methods: The study population consisted of parents of LUTO patients. Fathers over 50 years of age were excluded, to avoid inclusion of male phenocopies due to early prostatic hypertrophy. Uroflowmetry, ultrasonography for residual urine and hydronephrosis, and laboratory examination of standard renal retention parameters were assessed, and a detailed patient history was taken, including the assessment of the International Prostate Symptom Score. Results: Twenty-nine of 42 LUTO families enrolled were found eligible for the present study. Of these, we identified five families in which the father had already been diagnosed with infravesical obstruction (17%). Of the remaining families, nine agreed to participate in our study. Of these nine families, eight families had a child affected with PUV and one family had a child with urethral stenosis. Here, we found two fathers and one mother with symptoms of LUTO suggestive of mild LUTO and one family, in which the unborn male fetal brother of the affected index patient was also diagnosed prenatally with LUTO. Conclusion: Our observations suggest that LUTOs have a higher heritability than previously thought and that first-degree relatives of the affected should be clinically assessed for symptoms of LUTO.
CRIS-Team Scopus Importer:2024-04-05
Keywords: familial LUTO; IPSS; LUTO; obstructive uropathy; postvoid residual volume; PUV; uroflowmetry